Wireless communication networks and systems / Cory Beard, William Stallings. - Beard, Cory; Stallings, William (Pearson, 2016)
This title covers all types of wireless communications, from satellite and cellular to local and personal area networks. Organized into four easily comprehensible, reader-friendly parts, it presents a clear and comprehensive overview of the field of wireless communications.